Petrogenetic characteristics of mafic-ultramafic massifs in Nizhne-Derbinsk complex (East Sayan Mountains) - Cherkasova, Tamara Yurievna; Chernishov, A.; Goltsova, Yu.; Timkin, Timothy Vasilyevich; Abramova, Raisa Nikolaevna (IOP Publishing, 2015)
The article describes the results of petrographic, petrochemical, petrofabric, mineralogical and geochemical studies of the major rock groups potentially Cu, Ni, Pt ore- bearing mafic-ultramafic massifs in the Nizhne- Derbinsk complex (Eastern Sayan Mountains). Based on the data interpretation the investigated massifs can be classified as peridotite-pyroxenite-gabbronorite formation of geosynclinal regime in Altai-Sayan folding area. Significant massif deformation occurred during the final post-consolidation formation stage. The petrographic features of gabbro and petrofabric patterns of the rock-forming minerals in the Burlakski and Nizhne-Derbinsk massifs indicated the fact that massifs were involved in the accretion-collisional development stage of the Central Asian folding belt during the final formation stages the Nizhne-Derbinsk complex.
Keywords: Саяны; геохимические исследования; рудоносные массивы; габброиды; горные породы